CRANIAL OSTEOMYELITIS AS A COMPLICATION OF FURUNCULAR MYIASIS - Muñoz,Nelson (2021)
ABSTRACT Objective: To report the case of an infant with infrequent cranial osteomyelitis as a complication of furuncular myiasis. Case description: The patient was a 4-month-old male who presented to the emergency department with a nodular skull lesion with edema, tenderness, pain, and purulent drainage, as well as progress of the ulcerated lesion and evidence of larvae inside. Antibiotic treatment was initiated, and the patient was taken to the operating room to remove the larvae, but he had no symptomatic improvement. A skull radiograph was taken to visualize the osteolytic lesion, and a 3D computed tomography scan showed osteomyelitis of the external parietal surface. Antibiotic management readjustment continued for a total of six weeks, and a skin flap was used with clinical improvement. Comments: Myiasis is defined as the infestation of vertebrates with fly larvae. In mammals, larvae can feed on host tissue and cause a wide range of infestations depending on their location in the body. The cranial osteomyelitis as a complication of myiasis described in this report seems to be an exceptional case.